Complex Systems, Sustainability and Innovation 2016
DOI: 10.5772/66453
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Complex Systems, Sustainability and Innovation

Abstract: The technological innovations have always proved the impossible possible. Humans have all the time obliterated barriers and set records with astounding regularity. However, there are issues springing up in terms of complexity and sustainability in this context, which we were ignoring for long. Today, in every walk of life, we encounter complex systems, whether it is the Internet, communication systems, electrical power grids, or the financial markets. Due to its unpredictable behavior, any creative change in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…So we explored the emergence of brain regions in terms of negative degree distribution. Emergent property explained that individuals may work differently from the whole in a complex system 44 . We found that the negative degree distribution of some brain regions significantly differed from the degree distribution of the whole brain.…”
Section: Effect Of Topology On the Balancementioning
confidence: 99%
“…So we explored the emergence of brain regions in terms of negative degree distribution. Emergent property explained that individuals may work differently from the whole in a complex system 44 . We found that the negative degree distribution of some brain regions significantly differed from the degree distribution of the whole brain.…”
Section: Effect Of Topology On the Balancementioning
confidence: 99%
“…Interdependence in complex systems, which arises from intricate connections existing between components can cause considerable systemic weakness too [3] [4]. Representing the complex systems using complex networks gives effective tools to study the emergent behaviour of these systems [5] [6]. When studying from the perspective of complex networks, it has been revealed that complex networks show similarities in their structure.…”
Section: Complex Systemmentioning
confidence: 99%
“…The unpredictable characteristic of chaos means that the objective is to stay on the sustainable state represented by the attractor [38]. Based on these senses, it is concluded that the phenomenon of chaos represents sustainability [39]. In fact, the theory of "edge of chaos " [40] shows that the system develops towards sustainability in a perpetual exploration of emergent order moving from chaos into order and back again.…”
Section: Introductionmentioning
confidence: 99%